Unraveling The Efforts of Gorontalo's POM Office Against Consumers Who Are Lost Due to Problematic Cosmetics Promotion on Instagram - Yutika Fitriyani Tomoolango; Mutia Cherawaty Thalib; Sri Nanang Meiske Kamba (Universitas Negeri Gorontalo, 2019)
Abstract:The purpose of this study was to find out how the Gorontalo’s POM Office efforts towards consumers who were harmed by the promotion of problematic cosmetics on Instagram. This study uses an empirical legal research method, which puts field facts as data. Sources of data used are primary data as the main data (the results of observations and interviews in the field), and secondary data such as legislation, and scientific works. Meanwhile, the population and the sample used were Gorontalo POM Office. The results showed that the efforts made by Gorontalo POM Office against consumers who were harmed by the promotion of cosmetics on Instagram were carried out in 2 (two) ways, namely legal protection with preventive measures by carrying out socialization, and other actions deemed correct and relevant; and legal protection with repressive measures carried out by providing guidance to business actors, confiscation of goods, to imposing sanctions and other measures deemed relevant.Keywords: Legal Protection; Consumer; Responsibility